Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
If that is 6-3(log2n)=0 then how you would go about solving it is by looking at log2n like x. In this case, for 6-3x=0, x would have to =2. So log2n has to =2. If log2n=2 and we assume that the base is 10 (because if there is no written base on a log then it is 10) then we need to rewrite the log to exponential form. Rewritten it's 10^2=2n. 100=2n, divide both sides by 2 and you get n=50.
[tex]6 - 3log2n = 0[/tex]
[tex]-3log2n = -6[/tex]
[tex]log2n = 2[/tex]
[tex] 10^{2} = 2n[/tex]
[tex]100 = 2n[/tex]
[tex]n = 50[/tex]
[tex]-3log2n = -6[/tex]
[tex]log2n = 2[/tex]
[tex] 10^{2} = 2n[/tex]
[tex]100 = 2n[/tex]
[tex]n = 50[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.